Engineers role in ensuring safety : 55th convention, Dhaka 2014 - Institution of Engineers (Bangladesh). Annual Convention 2014 : Dhaka, Bangladesh); Institution of Engineers (Bangladesh) (Dhaka : The Institution of Engineers, Bangladesh, 2014)
With a special reference to Bangladesh.
"Engineers for development: towards safer environment."
"National seminar theme: Engineers role in ensuring safety; 1-5 May, 2014"--Cover.
Includes bibliographical references.
Keywords: Engineering; Engineers